THE TRANSLATION STRATEGIES OF CULTURAL WORDS IN AHMAD TOHARI'S DANCER - Nitisari, Dwi (Universitas Gunadarma, 2016)
The aim ofthis research is to find out the translation strategies by examining twonovels, which are